1996
DOI: 10.1107/s0108768195008615
|View full text |Cite
|
Sign up to set email alerts
|

Rietveld structure refinements of calcium hydroxylapatite containing magnesium

Abstract: The crystal structures of four hydroxylapatite (HA) samples prepared from solutions in the presence of 10, 15, 25 and 30 Mg-atom-% have been investigated by X-ray powder pattern fitting. The total magnesium content of the solid samples, as determined by chemical analysis, was 4.9, 14.1, 20.4 and 30.6 Mg-atom-%, respectively. Rietveld analysis was performed using the computer program PREFIN implemented with routines which allow the refinements of the average crystallite sizes. Different refinement procedures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 18 publications
(34 reference statements)
4
51
0
1
Order By: Relevance
“…Such discrepancies might be due to differences in synthetic procedures (which could perhaps alter the final site for incorporated Mg), and/or to the low quality of the XRD patterns used in the Rietveld refinements. Indeed, it is noteworthy that some of the refined distances are surprising: for a sample with ~ 30% Mg, an average M•••O bond distance was found that was almost identical to the non-substituted compound, [20] which seems contradictory with the fact that average Recently, alternative approaches have started to emerge to investigate in more depth the mode of incorporation of substituting divalent cations in HA phases. In particular, it has been shown that much information could be accessed experimentally using spectroscopic techniques which are sensitive to the local structure around particular cations, such as X-ray absorption spectroscopy and solid state NMR.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Such discrepancies might be due to differences in synthetic procedures (which could perhaps alter the final site for incorporated Mg), and/or to the low quality of the XRD patterns used in the Rietveld refinements. Indeed, it is noteworthy that some of the refined distances are surprising: for a sample with ~ 30% Mg, an average M•••O bond distance was found that was almost identical to the non-substituted compound, [20] which seems contradictory with the fact that average Recently, alternative approaches have started to emerge to investigate in more depth the mode of incorporation of substituting divalent cations in HA phases. In particular, it has been shown that much information could be accessed experimentally using spectroscopic techniques which are sensitive to the local structure around particular cations, such as X-ray absorption spectroscopy and solid state NMR.…”
Section: Introductionmentioning
confidence: 94%
“…[15,21,22] The main difficulty in answering this question in the case of Mg-HA arises from the absence of high resolution spectroscopic data over an important range of composition, and the significant loss of crystallinity of Mg-HA compounds above ~ 20% Mg. Thus, in contrast with Sr-or Ba-substituted HA, [23,24] Rietveld analyses based on X-ray powder patterns are not conclusive for Mg-HA, and both the Ca(I) [15] and the Ca(II) [20] sites have been suggested to be the preferential site of incorporation of Mg. Such discrepancies might be due to differences in synthetic procedures (which could perhaps alter the final site for incorporated Mg), and/or to the low quality of the XRD patterns used in the Rietveld refinements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, let us quote Mg [56], Si [57], Cd [58], Sr [59] and Pb [60]. More precisely, Zhu et al [61] founded that the metal ions of Pb 2+ , Sr 2+ and Cd 2+ preferentially occupied Ca[II] sites in the apatite structure (two occupation sites exist as gathered in Table 1) .…”
Section: Considering Substitution Processesmentioning
confidence: 99%
“…It is well illustrated by temperature unstability of Mg-containing apatite [10,12]. The increase of Mg content in synthetic HA reduces temperature of phase decomposition with formation of magnesium substituted β-TCP (or β-TCMP) (Ca,Mg) 3 (PO 4 ) 2 , and the extent of HA conversion into β-TCMP on heat treatment appears strongly related to Mg amount of the apatitic solid phase [12][13][14]. In work [14] the conclusion is made, that whole Mg from nonequilibrium apatitic phase of the different HA samples enters (at Т=900 °C) the crystal structure of β-TCMP.…”
Section: Introductionmentioning
confidence: 97%